Effect of Ag addition on phase transitions of the Cu-22.26 at.%Al-9.93 at.%Mn alloy - Silva, R. A G; Gama, S.; Paganotti, A.; Adorno, A. T. [UNESP]; Carvalho, T. M. [UNESP]; Santos, C. M A [UNESP] (Elsevier, 2013)
The phase transitions that occur in the Cu-22.26 at.%Al-9.93 at.%Mn and Cu-22.49 at.%Al-10.01 at.%Mn-1.53 at.%Ag alloys after slow cooling were studied using differential scanning calorimetry at different heating rates, microhardness changes with temperature, magnetization changes with temperature, scanning electron microscopy and energy dispersion X-ray spectroscopy. The results indicated that the presence of Ag does not modify the transition sequence of Cu-Al-Mn alloy, introduces a new transition due to the (Ag-Cu)-rich precipitates dissolution at about 800 K, and changes the mechanism of DO 3 phase dissolution. This mechanistic change was analyzed and a sequence of phase transitions was proposed for the reaction. © 2013 Elsevier B.V.
Keywords: Metals and alloys; Phase transitions; Thermal analysis; Ag additions; Ag-alloy; Cu-Al-Mn alloy; Energy dispersions; Phase dissolution; Slow cooling; Transition sequences; Differential scanning calorimetry; Dissolution; Manganese; Metallurgy; Scanning electron microscopy; Silver; Silver alloys; Thermoanalysis; X ray spectroscopy; Aluminum